Altered hydroxymethylation is seen at regulatory regions in pancreatic cancer and regulates oncogenic pathways - Bhattacharyya, Sanchari; Pradhan, Kith; Campbell, Nathaniel; Mazdo, Jozef; Vasantkumar, Aparna; Maqbool, Shahina; Bhagat, Tushar D.; Gupta, Sonal; Suzuki, Masako; Yu, Yiting; Greally, John M.; Steidl, Ulrich; et al. (Genome Research, 2017)
Transcriptional deregulation of oncogenic pathways is a hallmark of cancer and can be due to epigenetic alterations. 5-Hydroxymethylcytosine (5-hmC) is an epigenetic modification that has not been studied in pancreatic cancer. Genome-wide analysis of 5-hmC-enriched loci with hmC-seal was conducted in a cohort of low-passage pancreatic cancer cell lines, primary patient-derived xenografts, and pancreatic controls and revealed strikingly altered patterns in neoplastic tissues. Differentially hydroxymethylated regions preferentially affected known regulatory regions of the genome, specifically overlapping with known H3K4me1 enhancers. Furthermore, base pair resolution analysis of cytosine methylation and hydroxymethylation with oxidative bisulfite sequencing was conducted and correlated with chromatin accessibility by ATAC-seq and gene expression by RNA-seq in pancreatic cancer and control samples. 5-hmC was specifically enriched at open regions of chromatin, and gain of 5-hmC was correlated with up-regulation of the cognate transcripts, including many oncogenic pathways implicated in pancreatic neoplasia, such as MYC, KRAS, VEGFA, and BRD4. Specifically, BRD4 was overexpressed and acquired 5-hmC at enhancer regions in the majority of neoplastic samples. Functionally, acquisition of 5-hmC at BRD4 promoter was associated with increase in transcript expression in reporter assays and primary samples. Furthermore, blockade of BRD4 inhibited pancreatic cancer growth in vivo. In summary, redistribution of 5-hmC and preferential enrichment at oncogenic enhancers is a novel regulatory mechanism in human pancreatic cancer.
10.1101/gr.222794.117